Cover Picture: A New Method for Predicting the Detonation Velocity of Explosives with Micrometer Aluminum Powders (Prop., Explos., Pyrotech. 4/2018). Issue 4 (23rd April 2018) - Li, Xing‐Han; Zhao, Feng; Qin, Jin‐Cheng; Pei, Hong‐Bo
Abstract : The cover picture shows that a new method, which relies on velocity and temperature disequilibrium between aluminum powders (Al) and explosives, could predict detonation velocity (VOD) of explosives with micrometer Al additives, precisely. The computed VODs constitute a 3D envelope for NM‐, TNT‐, RDX‐ and HMX‐based aluminized explosives, respectively. As the envelopes show in the cover picture, the calculated VOD varies with the size and mass percent of Al powders in a non‐linear way, and it reaches a great agreement with experimental results, which are represented by the light pillars. More details can be found in the article by Xing‐Han Li and Hong‐Bo Pei et al. on page 333 ff.